KISAH KECIL: MEMOTRET ANAK DENGAN PENDEKATAN PARTISIPAN - Tohari Tohari; Alysha Purnamasari (Institut Seni Budaya Indonesia Bandung, 2021)
Children's daily activities will not be finished to be produced into a photo, there are expressions with all forms of overflow, games, learning activities at school and at home, work, cooking, to activities to help parents, is a moment that can be used as a source of photography creation. The process of making photos of children must be done with an approach, participants who are more appropriate to approach and adapt to children. Photographers must be pro-active in following and directly involved in each child's activities. The goal is that the shooting becomes smooth, and there is no boredom for children who are used as the subject of the photo shoot. Difficulties in photographing children can be nullified if there is a fabric of good communication between the photographer and the child. Photographers must look for findings that are used as sources of children's photography creation ideas, for example what activities children often do, then how their expressions are, and how to approach techniques with the subject in the photo shoot. In addition to the approach, the process of creating photos of children requires methods, which are divided into pre-production, production, and post-production, which are almost all practices. Small Story: Photographing Children with Participatory Approaches, providing comments and practices for making photographs, with children as a source of creation. Children's daily activities, such as swimming, biking, gathering, playing, and other children's activities have been portrayed by the photographer with his camera, plus an overflowing form of child expression: crying and laughing, making the photo appearance of the child attractive.